Health-related quality-of-life in a randomized phase III first-line study of gefitinib versus carboplatin/paclitaxel in clinically selected patients from Asia with advanced NSCLC (IPASS) - Thongprasert S. (2014)
Introduction: Evaluation of health-related quality-of-life (HRQoL) and symptom improvement were preplanned secondary objectives for the overall population and posthoc analyses for epidermal growth factor receptor (EGFR) mutation-positive/negative subgroups in IPASS. Methods: HRQoL was assessed using the Functional Assessment of Cancer Therapy-Lung (FACT-L) and Trial Outcome Index (TOI); symptom improvement by the Lung Cancer Subscale (LCS). Improvements defined as: 6 or more (FACT-L; TOI), 2 or more (LCS) points increase maintained for 21 or more days. Results: Overall (n = 1151/1217 evaluable), HRQoL improvement rates were significantly greater with gefitinib versus carboplatin/paclitaxel; symptom improvement rates were similar for both treatments. Significantly more patients recorded improvements in HRQoL and symptoms with gefitinib in the EGFR mutation-positive subgroup (n = 259; FACT-L 70.2% versus 44.5%; odds ratio, 3.01 [95% confidence interval, 1.79-5.07]; p < 0.001; TOI 70.2% versus 38.3%; 3.96 [2.33-6.71]; p < 0.001; LCS 75.6% versus 53.9%; 2.70 [1.58-4.62]; p < 0.001), and with carboplatin/paclitaxel in the EGFR mutation-negative subgroup (n = 169; FACT-L 14.6% versus 36.3%; odds ratio, 0.31 [0.15-0.65]; p = 0.002; TOI 12.4% versus 28.8%; 0.35 [0.16-0.79]; p = 0.011; LCS 20.2% versus 47.5%; 0.28 [0.14-0.55]; p < 0.001). Median time-to-worsening (months) FACT-L score was longer with gefitinib versus carboplatin/paclitaxel for the overall population (8.3 versus 2.5) and EGFR mutation-positive subgroup (15.6 versus 3.0), and similar for both treatments in the EGFR mutation-negative subgroup (1.4 versus 1.4). Median time-to-improvement with gefitinib was 8 days in patients with EGFR mutation-positive tumors who improved. Conclusions: HRQoL and symptom endpoints were consistent with efficacy outcomes in IPASS and favored gefitinib in patients with EGFR mutation-positive tumors and carboplatin/paclitaxel in patients with EGFR mutation-negative tumors. Copyright © 2011 by the International Association for the Study of Lung Cancer.